2010
DOI: 10.1111/j.1365-2745.2010.01710.x
|View full text |Cite
|
Sign up to set email alerts
|

A 350‐year tree‐ring fire record from Białowieża Primeval Forest, Poland: implications for Central European lowland fire history

Abstract: Summary1. Fires are nowadays small, yet frequent, in temperate Central European conifer forests, but little is known about the fire history in this region. This is likely due to the lack of intact forests that contain old trees and dead wood from which fire history may be reconstructed. An exception is the Białowie_ za Primeval Forest (BPF) in Poland for which we were able to reconstruct the fire history in detail. 2. From 886 tree ring samples collected in a 13-ha conifer-dominated area, we reconstructed fire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
136
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(147 citation statements)
references
References 68 publications
(160 reference statements)
6
136
1
4
Order By: Relevance
“…Empirical research on post-fire regeneration dynamics conducted in several sub-Mediterranean areas of Iberia have shown that P. sylvestris and P. nigra stands have been replaced by Quercus woodlands, shrublands or even grasslands several years or decades after the occurrence of wildfire (Retana et al 2002;Rodrigo et al 2004;Pérez-Cabello et al 2010). These Iberian data on the tolerance of P. sylvestris to fire and on the post-fire regeneration dynamics of the species are in marked contrast with data from the boreal forests of Eurasia, where P. sylvestris is the most fire-tolerant tree and is, therefore, commonly favoured by recurrent fires (Agee 1998;Niklasson et al 2010). In fact, Picea abies becomes the dominant tree species in Eurasian boreal forests if the fire frequency and intensity decrease, and this species pushes P. sylvestris into the background (Niklasson and Drakenberg 2001).…”
Section: Responses Of Highland Pines To Fire and Anthropogenic Pressurementioning
confidence: 61%
See 1 more Smart Citation
“…Empirical research on post-fire regeneration dynamics conducted in several sub-Mediterranean areas of Iberia have shown that P. sylvestris and P. nigra stands have been replaced by Quercus woodlands, shrublands or even grasslands several years or decades after the occurrence of wildfire (Retana et al 2002;Rodrigo et al 2004;Pérez-Cabello et al 2010). These Iberian data on the tolerance of P. sylvestris to fire and on the post-fire regeneration dynamics of the species are in marked contrast with data from the boreal forests of Eurasia, where P. sylvestris is the most fire-tolerant tree and is, therefore, commonly favoured by recurrent fires (Agee 1998;Niklasson et al 2010). In fact, Picea abies becomes the dominant tree species in Eurasian boreal forests if the fire frequency and intensity decrease, and this species pushes P. sylvestris into the background (Niklasson and Drakenberg 2001).…”
Section: Responses Of Highland Pines To Fire and Anthropogenic Pressurementioning
confidence: 61%
“…Thus, P. sylvestris -dominated forests in boreal areas are commonly affected by low-to moderate-severity fire regimes characterised by ground fires, as revealed by studies conducted during the past decades on long-term fire ecology (Agee 1998) and by the frequent occurrence of individuals with multiple fire scars (Agee 1998;Niklasson and Drakenberg 2001;Niklasson et al 2010). The humid climate and the abundance of mires in these northern coniferous forests promote a post-fire heterogeneous landscape that favours P. sylvestris regeneration (Agee 1998).…”
Section: Responses Of Highland Pines To Fire and Anthropogenic Pressurementioning
confidence: 99%
“…One of the most important factors influencing the dynamics, species composition and structure of the Białowie_ za forests in the past was frequent but low energy fires, mostly caused by man, either beekeepers, charcoaltar-potash manufacturers, or herd wardens (Harnak 1764 after Hedemann 1939;Samojlik and Jędrzejewska 2004;Niklasson et al 2010). According to Brincken (1826), fires in the Białowie_ za Forest occurred almost on the annual basis.…”
Section: Discussionmentioning
confidence: 99%
“…The mean, minimum, and maximum fire intervals and the fire index, which is the percentage of scarred trees of the total number of analyzed trees in a certain fire year, were determined. A fire card (Grissino-Mayer et al, 2001;Niklasson et al, 2010) was created showing the fires on the five cross-sections.…”
Section: Methodsmentioning
confidence: 99%
“…The fire card and fire index obtained using 5 tree cross-sections from two different sites. Fire index is the percentage of scarred trees of the total number of analyzed trees in a certain fire year (Niklasson et al, 2010).…”
Section: Detection Of Fire Yearsmentioning
confidence: 99%